Phocine Distemper in German Seals, 2002 - Müller, Gundi; Wohlsein, Peter; Beineke, Andreas; Haas, Ludwig; Greiser-Wilke, Irene; Siebert, Ursula; Fonfara, Sonja; Harder, Timm; Stede, Michael; Gruber, Achim.D.; Baumgärtner, Wolfgang
Approximately 21,700 seals died during a morbillivirus epidemic in northwestern Europe in 2002. Phocine distemper virus 1 was isolated from seals in German waters. The sequence of the P gene showed 97% identity with the Dutch virus isolated in 1988. There was 100% identity with the Dutch isolate from 2002 and a single nucleotide mismatch with the Danish isolate.